Funding the cooperative city. Community finance and the economy of civic spaces. - (:unkn) unknown (My University, 2017)
Das Buch stellt Beispiele für urbane Alternativökonomie im Immobiliensektor aus ganz Europa vor. Daneben liefert es Hinweise für gemeinnützige Organisationen, EU-Institutionen, Bauträger und Gemeinden, die gemeinschaftliche Nutzungen öffentlicher Räume fördern möchten.

Funding the Cooperative City explores how citizen initiatives, cooperatives, non-profit companies, community land trusts, crowdfunding platforms, ethical banks and anti-speculation foundations step out of the regular dynamisms of real estate development and arrange new mechanisms to access, purchase, renovate or construct buildings for communities. Through interviews and analyses, this book describes tendencies and contexts, and presents stories and models of community finance and civic economy. It offers a helpful set of resources not only for community organisations and initiators of civic spaces, but also for private developers, municipalities and EU institutions that are willing to support, facilitate or cooperate with them in order to create more resilient and inclusive local communities, facilities and services.
Keywords: Stadtentwicklung; Kooperation; Finanzierung; Öffentlicher Raum; Raumnutzung; Gemeinschaftsnutzung; Nutzungsart; Kultureinrichtung; Öffentliche Einrichtung; Beispielsammlung; Zivilgesellschaft; Crowdfunding; Projektfinanzierung; Selbstorganisation; Organisationsmodell; Kleinunternehmen; Alternativökonomie; Alternativwirtschaft; Kunst im öffentlichen Raum